Les illusions perdues de la Mompreneur - Julie Landour (La Nouvelle Revue du Travail)
Over the years, self-employment has increasingly come to be seen as a remedy to joblessness. Yet until the late 1970s the model had been in decline. Nowadays, however, a number of advantages are associated with it. A variety of measures are being implemented to make it more accessible, notably to women who are still under-represented in this field. Nathalie is one of these new businesswomen, often referred to as Mompreneurs. Her narrative reveals the flip side of today’s general promotion of self-employment, showing that independent businesses can only be sustainable if they have solid social and economic resources to rely upon.